Nurturing Resilient Generations: Character Education in Islamic Teachings within the Framework of Society 5.0 - Irlina, Andi; Barni, Mahyuddin; Basir, Abd.; Khairuddin (IAIN Parepare, 2024)
In the 4.0 industrial revolution era, people need to be technology literate. This is carried out in light of the fact that people frequently utilize technology to make a variety of tasks or activities easier, including educational tasks. Technology can also help societies in a country to meet other societies around the words using varieties of social media platforms. Technology enlighten the 5.0 society’s task, but the existence of digital technology also causes children and teenagers to face a variety of issues; it impedes their development and progress, and it leads to negative behavior among children and teenagers. Violence, online gambling, free sex, killing for the sake of money, even, and suicide. In the 5.0 society era, however, a resilient generation is required. We need human resources that can not only utilize technology to make life easier but also use it to benefit people and the environment in order to meet the challenges of this new era. Qualitative methodologies and a literature review are used in this study. For this study, the author gathers and examines information from a number of trustworthy sources. The study's findings suggest that teaching Islamic character building education to children and teenagers is essential to prepare them to be resilient adults. Islam teaches about morality, adab, seerah, muroqabalah, worship, and monotheism. Communities, families, and educational institutions as well as the government can work together to establish character education initiatives that are in line with Islamic beliefs. Islamic character education offer insights into developing a resilient mindset that withstands technology disruptions and societal upheavals by utilizing a holistic viewpoint that takes into account people's spiritual, intellectual, and emotional aspects resulting resilient generations.